The Political Economy of Mitigation and Adaptation - Wolfgang Habla; Kerstin Roeder (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper, we acknowledge that the mitigation of and adaptation to climate change have differential fiscal impacts. Whereas mitigation typically raises fiscal revenues, adaptation is costly to the taxpayer and to a greater extent the more distortionary the tax system is. In an OLG model with majority voting, we analyze how the choices of mitigation and adaptation are distorted under a lump-sum and a distortionary income tax regime. We find that whenever emissions and adaptation exhibit stock characteristics, the levels of mitigation and adaptation are chosen inefficiently low in the political equilibrium under lump-sum taxation. By contrast, the political equilibrium may entail inefficiently high mitigation or inefficiently high adaptation (but not both simultaneously) if the tax system is distortionary. A calibration of our model to the German economy shows that both mitigation and adaptation can be expected to be inefficiently low in the political equilibrium. Furthermore, the standard assumption of a lump-sum tax system when analyzing mitigation and adaptation is found to underestimate the loss in utilitarian welfare relative to a distortionary tax system, although mitigation levels are generally higher under the latter regime.
Keywords: D72; D78; H21; H23; Q58; 330; adaptation; mitigation; political economy; majority voting; OLG; environmental taxes